Analysis of injuries in competitive equestrian events - Haines, C.; Jensen, H. K.; Karim, S. A.; McGhee, L. (Clinical Journal of Sport Medicine, 2022)
Objective: Current equestrian sport-related acute injury research is sparse. The goal of this study is to explore equestrian injury types stratified by population and equestrian discipline.